HISTORICAL THINKING AS A MAIN MECHANISM IN DEVELOPING A SENSE OF NATIONAL IDENTITY IN ADOLESCENT STUDENTS - Barlikbaevna, Toremuratova Gulnaz (Journal of Learning on History and Social Sciences, 2025)
Objective: This study aims to analyze the characteristics and types of historical thinking—specifically presentism, passeism, and futurism—and evaluate their influence on the development of national identity among adolescent students in Uzbekistan. Method: A qualitative approach was employed, integrating psychological, philosophical, and didactic analyses to explore how structured historical knowledge, context-rich content, and imaginative engagement contribute to identity formation. Results: The findings reveal that nurturing historical thinking significantly enhances students’ analytical skills, deepens their personal connection to historical narratives, and fosters critical reflection and value-based understanding of the past. Structured historical education not only strengthens students' cognitive engagement but also promotes emotional identification with national heritage, thereby facilitating socialization within a multiethnic society. Novelty: This study uniquely combines psychological and philosophical perspectives with didactic strategies to offer a comprehensive classification of historical thinking, providing theoretical and practical insights for educators seeking to cultivate historical consciousness, national pride, civic awareness, and cultural continuity in diverse educational environments.